Light Scattering and Current Enhancement for Microcrystalline Silicon Thin-Film Solar Cells on Aluminium-Induced Texture Glass Superstrates with Double Texture. (8th June 2015) - Yin, Yunfeng; Sahraei, Nasim; Venkataraj, Selvaraj; Calnan, Sonya; Ring, Sven; Stannowski, Bernd; Schlatmann, Rutger; Aberle, Armin G.; Stangl, Rolf
Abstract : Microcrystalline silicon ( μ c-Si:H) thin-film solar cells are processed on glass superstrates having both micro- and nanoscale surface textures. The microscale texture is realised at the glass surface, using the aluminium-induced texturing (AIT) method, which is an industrially feasible process enabling a wide range of surface feature sizes (i.e., 700 nm–3 μ m) of the textured glass. The nanoscale texture is made by conventional acid etching of the sputter-deposited transparent conductive oxide (TCO). The influence of the resulting "double texture" on the optical scattering is investigated by means of atomic force microscopy (AFM) (studying the surface topology), haze measurements (studying scattering into air), and short-circuit current enhancement measurements (studying scattering into silicon). A predicted enhanced optical scattering efficiency is experimentally proven by a short-circuit current enhancementΔ I sc of up to 1.6 mA/cm 2 (7.7% relative increase) compared to solar cells fabricated on a standard superstrate, that is, planar glass covered with nanotextured TCO. Enhancing the autocorrelation length (or feature size) of the AIT superstrates might have the large potential to improve the μ c-Si:H thin-film solar cell efficiency, by reducing the shunting probability of the device while maintaining a high optical scattering performance.